Lake-sediment record of PAH, mercury, and fly-ash particle deposition near coal-fired power plants in Central Alberta, Canada. (December 2017) - Barst, Benjamin D.; Ahad, Jason M.E.; Rose, Neil L.; Jautzy, Josué J.; Drevnick, Paul E.; Gammon, Paul R.; Sanei, Hamed; Savard, Martine M.
Abstract: We report a historical record of atmospheric deposition in dated sediment cores from Hasse Lake, ideally located near both currently and previously operational coal-fired power plants in Central Alberta, Canada. Accumulation rates of spheroidal carbonaceous particles (SCPs), an unambiguous marker of high-temperature fossil-fuel combustion, in the early part of the sediment record (pre-1955) compared well with historical emissions from one of North America's earliest coal-fired power plants (Rossdale) located ∼43 km to the east in the city of Edmonton. Accumulation rates in the latter part of the record (post-1955) suggested inputs from the Wabamun region's plants situated ∼17–25 km to the west. Increasing accumulation rates of SCPs, polycyclic aromatic hydrocarbons (PAHs) and Hg coincided with the previously documented period of peak pollution in the Wabamun region during the late 1960s to early 1970s, although Hg deposition trends were also similar to those found in western North American lakes not directly affected by point sources. A noticeable reduction in contaminant inputs during the 1970s is attributed in part to technological improvements and stricter emission controls. The over one hundred-year historical record of coal-fired power plant emissions documented in Hasse Lake sediments has provided insight into the impact that both environmental regulations and changes in electricity output have had over time. This information is crucial to assessing the current and future role of coal in the world's energy supply. Graphical abstract: Highlights: Pre-1955 fluxes of SCPs coincided with the history of coal combustion in Edmonton. Peak fluxes of contaminants coincided with peak pollution in the Wabamun region. Decreases in contaminant inputs in the 1970s credited to stricter emission controls. Abstract : A century of emissions from coal-fired power plants is recorded in sediments from a small lake in Central Alberta, Canada.